The influence of process parameters on the microstructure and properties of the TiC/Ti-alloy composites fabricated by the directed energy deposition process - Wang, Yongxia (2025)
In titanium matrix composites, the size and distribution of the reinforcing particles significantly impact their mechanical properties. Accordingly, in this work, TiC-reinforced Ti-alloy matrix composites were fabricated using the directed energy deposition (DED) technology. The influence of the varying process parameters on the microstructure and properties of the TiC-reinforcing particles and the α phase in the matrix was elucidated. The results revealed that process parameters had a notable influence on the morphology and distribution of the TiC reinforcing particles as well as the morphology of the α phase. A reduction in the pulse current and increasing scanning speed led to a significant decrease in the size of TiC reinforcing particles but offered uniform distribution. Concurrently, the morphology of the α phase changes from coarse lath-like to slender lath-like to irregular block-like. The combination of the TiC particles and the α phase with distinct characteristics resulted in significant variations in the room-temperature tensile properties of the TiC/Ti-alloy composites. The tensile strength of the TiC/Ti-alloy composites exhibiting optimal performance in this work reached 1412 MPa, which is ∼28% higher than that of the forged Ti-alloy matrix (1100 MPa). This research offers the groundwork for a substantial enhancement in the overall properties of titanium matrix composites.